The PK‐Eye: A Novel In Vitro Ocular Flow Model for Use in Preclinical Drug Development. Issue 10 (24th June 2015) - Awwad, Sahar; Lockwood, Alastair; Brocchini, Steve; Khaw, Peng T.
<x xml:space="preserve">Abstract</x> A 2‐compartment in vitro eye flow model has been developed to estimate ocular drug clearance by the anterior aqueous outflow pathway. The model is designed to accelerate the development of longer‐acting ophthalmic therapeutics. Dye studies show aqueous flow is necessary for a molecule injected into the vitreous cavity to clear from the model. The clearance times of proteins can be estimated by collecting the aqueous outflow, which was first conducted with bevacizumab using phosphate‐buffered saline in the vitreous cavity. A simulated vitreous solution was then used and ranibizumab (0.5 mg) displayed a clearance time of 8.1 ± 3.1 days, which is comparable to that observed in humans. The model can estimate drug release from implants or the dissolution of suspensions as a first step in their clearance mechanism, which will be the rate‐limiting step for the overall resident time of a candidate dosage form in the vitreous. A suspension of triamcinolone acetonide (Kenalog®) (4.0 mg) displayed clearance times spanning 26–28 days. These results indicate that the model can be used to determine in vitro–in vivo correlations in preclinical studies to develop long‐lasting therapeutics to treat blinding diseases at the back of the eye. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3330–3342, 2015